2002
DOI: 10.1046/j.1468-3148.2002.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Efficacy of a Cognitive‐Behavioural Anger Management Group for Clients with Learning Disabilities

Abstract: Background  Fourteen clients with learning disabilities referred for anger management were randomly assigned to a treatment group and a waiting‐list control group. Methods  Treatment consisted of nine 2‐h group sessions, using brainstorming, role‐play and homework. Topics addressed included: the triggers that evoke anger; physiological and behavioural components of anger; behavioural and cognitive strategies to avoid the build‐up of anger and for coping with anger‐provoking situations; and acceptable ways of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 20 publications
(35 reference statements)
7
146
1
2
Order By: Relevance
“…These clinical referrals may be associated with the relatively small sample sizes found in most studies, ranging from as little as 14 (Willner, Jones, Tams, & Green, 2002) to 162 (Willner et al, 2013). (2006) delivered either an integrated bereavement intervention or traditional counselling to bereaved adults with IDs.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…These clinical referrals may be associated with the relatively small sample sizes found in most studies, ranging from as little as 14 (Willner, Jones, Tams, & Green, 2002) to 162 (Willner et al, 2013). (2006) delivered either an integrated bereavement intervention or traditional counselling to bereaved adults with IDs.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…However, while there is evidence that an understanding of the A-B-C model is associated with outcome from CBT (Safran et al, 1993), we still do not know whether this is also the case for people with IDs. Furthermore, various studies have shown strong links between verbal ability, and both readiness for CBT (Dagnan et al, 2000;Dagnan & Chadwick, 1997;Joyce et al, 2006;Reed & Clements, 1989;Sams, Collins, & Reynolds, 2006), as well as therapeutic gains (Willner, Jones, Tams, & Green, 2002). The currently available assessments and training methods (Dagnan et al, 2000;Joyce et al, 2006;Reed & Clements, 1989) rely heavily on verbal comprehension and may be too difficult for some people with moderate IDs.…”
Section: Can a Computerised Training Paradigm Assist People With Intementioning
confidence: 99%
“…2. Only two studies 39,42 used randomised allocation to groups, and one of these 39 was extremely small. 3.…”
Section: Anger In People With Intellectual Disabilitiesmentioning
confidence: 99%
“…Positive results were reported for two interventionscognitive reappraisal and problem-solving -but few further details are available. participants 39,41,42 (although this has been disputed), 49 and in participants who are accompanied to the group by a carer. 39,41 There is evidence that 'paraprofessionals', working under supervision following minimal training, can deliver effective manualised CBT.…”
Section: Anger In People With Intellectual Disabilitiesmentioning
confidence: 99%